Pets that Have ‘Something Inside’: The Material Politics of in/Animacy and Queer Kin within the Childhood Menagerie - Riikka Hohti; Jayne Osgood (Genealogy, 2020)
In this paper, we seek to unsettle and extend understandings of what constitutes the contemporary family in Western minority world society and consider the material politics that follow from such a reconceptualization. We do this by offering a situated exploration into the caring relations and shared biographies that routinely evolve between children, other than human animals and toys within the family home. An emergent field of scholarship (Hohti and Tammi 2019; Taylor 2011; Malone 2015) reveals child–animal relations to be charged with various pedagogical and ideological assumptions, which we argue are partly exported to the relations that form between children and their toys. We undertake a close examination of the relationalities between humans and a range of toys as a means to explore the ways in which care and liveliness materialize in childhood play and what this means for our conceptualizations of ‘the family’. We put to work the idea of queer worlding (Haraway 2008; Osgood and Andersen 2019) and animacy (Chen 2012) alongside Puig de la Bellacasa’s (2017, 2011) feminist ethics of care. We then specifically focus on the materiality of robotic toys to illustrate some crucial connectivities and erasures to examine how the queer human–animal and animate–inanimate boundaries are reworked and negotiated in childhood play. These processes create a shift in understanding what matters in children’s lives and how materiality and affective forces co-constitute the posthuman family. This paper engages critically with the ambivalences and tensions that emerge within the domestic menagerie and extend to a planetary scale in ways that are inherently political.